2008
DOI: 10.1007/s10661-008-0300-z
|View full text |Cite
|
Sign up to set email alerts
|

Water quality assessment and source identification of Daliao river basin using multivariate statistical methods

Abstract: Multivariate statistical methods, such as cluster analysis (CA), discriminant analysis (DA) and principal component analysis (PCA), were used to analyze the water quality dataset including 13 parameters at 18 sites of the Daliao River Basin from 2003-2005 (8424 observations) to obtain temporal and spatial variations and to identify potential pollution sources. Using Hierarchical CA it is classified 12 months into three periods (first, second and third period) and the 18 sampling sites into three groups (groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
118
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(124 citation statements)
references
References 28 publications
2
118
1
3
Order By: Relevance
“…During most of the time period covered by this study, the sluice gates were closed and water bodies were relatively stagnant, effectively eliminating any effects from upstream flushing and pollution sources. As the opening and closing of floodgates can alter pollutant concentrations, the change of pollutant concentrations between months observed in this study was not as predictable as in other studies unaffected by floodgate operations (Girija et al 2007;Zhang et al 2009). …”
Section: Comparison To Previous Researchcontrasting
confidence: 93%
See 3 more Smart Citations
“…During most of the time period covered by this study, the sluice gates were closed and water bodies were relatively stagnant, effectively eliminating any effects from upstream flushing and pollution sources. As the opening and closing of floodgates can alter pollutant concentrations, the change of pollutant concentrations between months observed in this study was not as predictable as in other studies unaffected by floodgate operations (Girija et al 2007;Zhang et al 2009). …”
Section: Comparison To Previous Researchcontrasting
confidence: 93%
“…Because the distribution of DO diverged so far from normality, this parameter was excluded from the analysis. For PCA all selected parameters were z-scale standardized (mean = 0 and variance = 1), which renders the data dimensionless and minimizes the effects of differences in measurement units and variance (Zhou et al 2007;Zhang et al 2009). Before the PCA analysis, the Kaiser-Meyer-Olkin (KMO) and Bartlett's Sphericity tests were performed on the parameter correlation matrix in order to examine the validity of the subsequent PCA.…”
Section: Water Quality Data Preparationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heavy metal pollutants have been considered to be one of the most critical global pollutants and pose a serious threat to human health and natural ecosystems (Lotze et al 2006;Li et al 2007;Li et al 2009;Fang et al 2009;Arik and Yaldiz 2010;Deng et al 2010;Naser 2013;Zhang et al 2009b). The first national soil pollution status survey bulletin released on April 17, 2014 launched by the Ministry of Environmental Protection and Ministry of Land and Resources of the People's Republic of China demonstrated that the ratio of exceeding soil standards in all of the samples is 16.1 % and the rate of arable land reaches 19.4 %, while the ratio of Cd is 7.0 % in all of the samples.…”
Section: Introductionmentioning
confidence: 99%